POLYSEMY IN THE LEXICAL-SEMANTIC FIELD "FITNESS" - Turaeva Madina Sultonbek qizi (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
The phenomenon of polysemy remains an intriguing subject in linguistic studies, particularly within specialized lexical-semantic fields such as "Fitness." Although polysemy, or multiple meanings in a single lexical unit, has been recognized and studied since the 19th century, its complexity and dynamic nature make it an ongoing area of interest. This article examines how polysemy functions in the lexical-semantic field of "Fitness" through the lens of classical linguistic theory and modern cognitive linguistics. Attention is paid to definitions and distinctions made by scholars such as A.I. Smirnitsky, A.Ya. Shaikevich, and Yu.D. Apresyan. A typological overview is provided, covering radial, chain, and metaphorically/metonymically motivated polysemy. Specific examples from authoritative English dictionaries illustrate how the term "fitness" and related words like "active" and "activeness" exhibit varying degrees of polysemy. The cognitive dimensions of polysemy are also considered, emphasizing the mental representation and categorization of concepts. Through this multifaceted analysis, the article underscores the relevance of polysemy in enriching and expanding the functional capacity of the "Fitness" lexicon.